2017
DOI: 10.13075/ijomeh.1896.00802
|View full text |Cite|
|
Sign up to set email alerts
|

Mobile phone use and risk for intracranial tumors and salivary gland tumors – A meta-analysis

Abstract: Results of epidemiological studies on the association between use of mobile phone and brain cancer are ambiguous, as well as the results of 5 meta-analysis studies published to date. Since the last meta-analysis (2009), new case-control studies have been published, which theoretically could affect the conclusions on this relationship. Therefore, we decided to perform a new meta-analysis. We conducted a systematic review of multiple electronic data bases for relevant publications. The inclusion criteria were: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
5
27
0
1
Order By: Relevance
“…Both reported evidence for an increased risk of glioma and schwannoma in exposed animals. These are the same two tumour types most strongly associated with wireless phone use [9]. Replicating a previous study, German researchers confirmed cancer promotion by RF in mice where this was linked to metabolic changes [18].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Both reported evidence for an increased risk of glioma and schwannoma in exposed animals. These are the same two tumour types most strongly associated with wireless phone use [9]. Replicating a previous study, German researchers confirmed cancer promotion by RF in mice where this was linked to metabolic changes [18].…”
supporting
confidence: 64%
“…A meta-analysis of 24 case-controlled studies (26,846 cases, 50,013 controls) showed a significantly increased risk of intracranial tumours (especially gliomas) associated with long-term use of mobile phones [9]. Despite some dismissing this risk based on the marginal increases in overall brain cancer incidence rates in populations, recent studies report a significant rise in the incidence rates of most aggressive high-grade gliomas, glioblastoma multiforme (GBM) which appears to be obscured in overall trends by a reduction of certain tumour types including lower-grade gliomas.…”
mentioning
confidence: 99%
“…Furthermore, while some published reports indicate that the carcinogenic effect of mobile phone radiation is more prominent for long‐term exposures (e.g., >5 or 10 years), Sato et al [] grouped their participants based on having or not having mobile phones only one year before diagnosis: “For analysis, patients were divided into 16 patients who were mobile phone owners 1 year before diagnosis and 66 patients who did not own mobile phones (non‐owners).” In this light, Prasad et al [] have recently provided evidence showing an association between mobile phone use and brain tumors, especially in people who used their mobile phones for more than 10 years. Bortkiewicz et al [] have also recently performed a meta‐analysis and reported that their findings supported the hypothesis that long‐term use of mobile phones was linked to increased risk of intracranial tumors.…”
mentioning
confidence: 79%
“…Previous meta‐analyses [Bortkiewicz, ; Bortkiewicz et al, ; Prasad et al, ] reported that the relative risk was 1.33 or 1.46 for a length of mobile phone use of 10 years or more. Therefore, in the present study, we conducted a simulation on mobile phone use of 10 years or more.…”
Section: Discussionmentioning
confidence: 99%